Hand function in female patients with hand osteoarthritis: relation with radiological progression - Ceceli, Esma (Springer-Verlag, 2012)
OBJECTIVE: We aimed to investigate the effect of hand osteoarthritis (HOA) on hand strength, dexterity, and upper extremity functional scores, as well as to determine the relation of radiological severity of HOA with these parameters. METHODS: Sixty patients and 40 controls were enrolled in the study. The presence of hand pain, nodes, and tenderness in hand joints was determined. Grip and pinch strengths were measured by Jamar dynamometer and pinch meter, dexterity was assessed by Purdue pegboard test, and upper extremity function was determined by disabilities of arm, shoulder and hand (DASH) test. Hand radiographs were evaluated according to the Kallman grading scale. RESULTS: The mean age of the patients and control subjects were 58.9 ± 4.8 and 56.6 ± 5.8 years, respectively. The level of hand pain and tenderness, and the number of nodes were significantly higher in the patient group than in control subjects. The mean grip and pinch strengths were lower in the patient group,: however, the difference was significant only in left lateral and left three chuck pinch. In hand dexterity, all scores except Purdue 1 were significantly lower in the patient group. In the functional evaluation DASH outcome, questionnaire scores of the patient and control groups were 48.3 ± 26.3 and 39.5 ± 23.5, respectively (p > 0.05). In the patient group, Kallman scores indicating radiological severity were found to be correlated with age, DASH scores, grip and pinch strengths, and Purdue scores (except Purdue assembly). Pain by visual analog scale was significantly higher in the patient group and correlated significantly with DASH scores. CONCLUSION: In patients with HOA, using standardized tests for evaluations may not be adequate. The determination of grip–pinch strength, dexterity and functional disability will lead to a clearer definition of the needs of the patients and will likely increase the gains from the rehabilitation programs.